Righteous Jehu and his evil heirs the Deuteronomist's negative perspective on dynastic succession - Lamb, David T. (David Trout), 1962-; Oxford eBooks (Oxford : Oxford University Press, 2007)
David T. Lamb discusses religious aspects of kingship (such as anointing, divine election, and prayer) in both the Old Testament and in the literature of the ancient Near East.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jehu, -- King of Israel; Bible. -- Criticism, interpretation, etc; Kings and rulers -- Succession -- Biblical teaching; Israel -- Kings and rulers -- Succession; Electronic books